Assisted reproductive techniques do not impact late neurodevelopmental outcomes of preterm children - Lefebvre, Tiphaine; Flamant, Cyril; Olivier, Marion; Gascoin, Géraldine; Bouet, Pierre-Emmanuel; Roze, Jean-Christophe; Barrière, Paul; Fréour, Thomas; Muller, Jean-Baptiste (Frontiers in Pediatrics, 2023)
Assisted Reproductive Technology (ART) increase the rate of preterm births, though few studies have analysed outcomes for these infants. No data is available on 4 years old children born prematurely after ART. The objective was to investigate whether ART affect neurodevelopmental outcomes at 4 years in preterm infants born before 34 weeks of gestational age (GA). Methods: A total of 166 ART and 679 naturally conceived preterm born before 34 weeks GA between 2013 and 2015 enrolled in the Loire-Infant-Follow-up-Team (LIFT) were included. Neurodevelopment was assessed at 4 years using the Age and Stage Questionnaire (ASQ) and need for therapy services. Association between the socioeconomic and perinatal characteristics and non-optimal neurodevelopment at 4 years was estimated. After adjustment, ART preterm group remained significantly associated with a lower risk of having at least two domains in difficulty at ASQ: aOR 0.34, 95%CI [0.13, 0.88], p =0.027. Factors independently associated with non-optimal neurodevelopment at 4 years were male gender, low socio-economic level and GA at birth 25-30 weeks. Need for therapy services was similar between groups (p=0.079). Long term neurodevelopmental outcomes of preterm children born after ART are very similar, or even better to that of spontaneously conceived children.